SISTEM POINT OF SALE BERBASIS WEB PADA BUTIK TUFFAHYZ - Haryanto, Teguh (JATISI, 2024)
This research developed a web-based point of sale (POS) system for Tuffahyz stores. The main goal of this system is to improve the efficiency and accuracy of managing in-store sales transactions that were previously done manually. This POS system is designed using the Waterfall system development methodology which includes planning, designing, implementation, verification, and maintenance stages. This study uses observation, interviews, and document analysis as data collection methods. The system built allows store owners, administrators and cashiers to manage sales transactions, track reports and manage product inventory more easily. The test results showed that this point of sale system worked as expected, helping to improve the performance and efficiency of the store. It is hoped that this system can improve the quality of service to customers and support the business development of Tuffahyz stores.